2015
DOI: 10.7202/1034142ar
|View full text |Cite
|
Sign up to set email alerts
|

Grief & Loss Resolution among Birth Mothers in Open Adoption

Abstract: While research has explored birth parent grief and loss, it has not been thorough in exploring how the experience of having an open adoption affects birth parents’ grief and loss experience and resolution. Previous research has highlighted positive effects of open adoptions to date, but is quite limited in regards to the birth parents’ adjustment in current day, open adoptions. This descriptive, qualitative study explores birth parents’ experiences in current day, open adoptions and seeks to understand their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…For example, as with many major life decisions, a birth mother can experience grief and other painful emotions that ebb and flow with time and circumstance but still be confident in the knowledge that she made the best choice for child. This conclusion parallels those drawn in Krahn and Sullivan’s (2015) study, where only 1 of the 13 birth mothers interviewed explicitly expressed regret about her decision, but there were expressions of differing degrees of guilt and sadness about their child’s adoption.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…For example, as with many major life decisions, a birth mother can experience grief and other painful emotions that ebb and flow with time and circumstance but still be confident in the knowledge that she made the best choice for child. This conclusion parallels those drawn in Krahn and Sullivan’s (2015) study, where only 1 of the 13 birth mothers interviewed explicitly expressed regret about her decision, but there were expressions of differing degrees of guilt and sadness about their child’s adoption.…”
Section: Discussionsupporting
confidence: 80%
“…This finding mirrors results found in the MTARP by McRoy and colleagues (2007), which found that birth mothers who had contact with their child experienced greater satisfaction. Prior research suggests that for some birth mothers, having contact with the child helps reduce feelings of anxiety about the child’s life and well-being, worries they may be having about the child feeling abandoned, and/or guilt about their decision (Krahn & Sullivan, 2015; Wiley & Baden, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations